Constraining sleptons at the LHC in a supersymmetric low-scale seesaw scenario - Cerna Velazco, Nhell Heder (2017)
The discovery of the Higgs boson in the 8 TeV run of the LHC [1, 2] marks one of the most important milestones in particle physics. Its mass is already known rather precisely: mh = 125.09 ± 0.21 (stat.) ±0.11 (syst.) GeV [3], and the signal strength of various LHC searches has been found consistent with the SM predictions. While this completes the Standard Model (SM) particle-wise, several questions still remain open, for example: (i) Is it possible to include the SM in a grand unified theory where all gauge forces unify? (ii) Is there a particle physics explanation of the observed dark matter relic density? (iii) What causes the hierarchy in the fermion mass spectrum and why are neutrinos so much lighter than the other fermions? What causes the observed mixing patterns in the fermion sector? (iv) What stabilizes the Higgs mass at the electroweak scale? Supersymmetric model address several of these questions and consequently the search for supersymmetry (SUSY) is among the main priorities of the LHC collaborations. Up to now no significant sign for physics beyond SM has been found. The combination of the Higgs discovery with the (yet) unsuccessful searches has led to the introduction of a model class called ‘natural SUSY’ [4–15]. Here, the basic idea is to give electroweak-scale masses only to those SUSY particles giving a sizeable contribution to the mass of the Higgs boson, such that a too large tuning of parameters is avoided. All other particle masses are taken at the multi-TeV scale. In particular, masses of the order of a few hundred GeV up to about one TeV are assigned to the higgsinos (the partners of the Higgs bosons), the lightest stop (the partner of the top-quark) and, if the latter is mainly a left-stop, also to the light sbottom In addition the gluino and the heavier stop masses should also be close to at most a few TeV. Neutrino oscillation experiments confirm that at least two neutrinos have a non-zero mass. The exact mass generation mechanism for these particles is unknown, and both the SM and the MSSM remain agnostic on this topic. Although many ways to generate neutrino mass exist, perhaps the most popular one is the seesaw mechanism [16–21]. The main problem with the usual seesaw mechanisms lies on the difficulty in testing its validity. In general, if Yukawa couplings are sizeable, the seesaw relations require Majorana neutrino masses to be very large, such that the new heavy states cannot be produced at colliders. In contrast, if one requires the masses to be light, then the Yukawas need to be small, making production cross-sections and decay rates to vanish. A possible way out of this dilemma lies on what 3 is called the inverse seesaw [22], which is based on having specific structures on the mass matrix (generally motivated by symmetry arguments) to generate small neutrino masses. This, at the same time, allows Yukawa couplings to be large, and sterile masses to be light. We consider here a supersymmetric model where neutrino data are explained via a minimal inverse seesaw scenario where the gauge-singlet neutrinos have masses in the range O(keV) to O(100 GeV). We explore this with a parametrization built for the standard seesaw, and go to the limit where the inverse seesaw emerges, such that Yukawas and mixings become sizeable. Although non-SUSY versions of this scenario can solve the dark matter and matter-antimatter asymmetry problems [23–25], we shall make no claim on these issues in our model. In view of the naturalness arguments, we further assume that the higgsinos have masses of O(100 GeV), whereas the gaugino masses lie at the multi-TeV scale (see [26] for an example of such a scenario). In addition, we assume all squarks are heavy enough such that LHC bounds are avoided, and play no role in the phenomenology within this work1. In contrast we allow for fairly light sleptons and investigate the extent to which current LHC data can constrain such scenarios. This paper is organized as follows: in the next section we present the model. Section III summarizes the numerical tools used and gives an overview of the LHC analysis used for these investigations. In Section IV we present our findings for the two generic scenarios which differ in the nature of the lighest supersymmetric particle (LSP): a Higgsino LSP and a sneutrino LSP. In Section V we draw our conclusions. Appendices A and B give the complete formulae for the neutrino and sneutrino masses.